Christ-centered preaching : redeeming the expository sermon - Chapell, Bryan (Grand Rapids, Michigan : Baker Academic, 2018)
In this complete guide to expository preaching, Bryan Chapell teaches the basics of preparation, organization, and delivery--the trademarks of great preaching. This new edition of a bestselling resource, now updated and revised throughout, shows how Chapell's case for expository preaching reaches twenty-first-century readers. -- !c From publisher's description
Includes bibliographical references and index
Keywords: Bible -- Homiletical use; Preaching